2007
DOI: 10.1007/s11434-007-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Coupling and propagating of mesoscale sea level variability between the western Pacific and the South China Sea

Abstract: The coupling and propagating features of mesoscale sea level variability between the western Pacific (WP) and the South China Sea (SCS) were studied based on time series analyses of satellite altimeter measured, along-track sea surface height anomalies (SSHA) along 21°N and the slope of the northern SCS. The analyses show that mesoscale sea level fluctuations in the WP have rather limited coherent effects on the SCS, and no statistically significant propagation of mesoscale variability through the Luzon Strait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…But the propagation velocities diminish to nearly zero at 122°E and 121°E in observations and simulations, respectively. It suggests that the directly westward propagation from the Pacific to the NSCS is not significant (Li et al, 2007).…”
Section: The Annual Mean Patternmentioning
confidence: 95%
See 2 more Smart Citations
“…But the propagation velocities diminish to nearly zero at 122°E and 121°E in observations and simulations, respectively. It suggests that the directly westward propagation from the Pacific to the NSCS is not significant (Li et al, 2007).…”
Section: The Annual Mean Patternmentioning
confidence: 95%
“…So a 21-175 days band-pass filter is used to remove the low-frequent variability and suppress synoptic disturbances with periods shorter than 20 days. An additional harmonic filter is then applied to remove the possible tidal aliasing near 60-day (Li et al, 2007). This frequency band is similar to the MV definition in Wang et al (2000) except that they have to remove all signals shorter than 60 days due to strong tidal aliasing in previous altimetry products.…”
Section: Product From the Eddy-resolving Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hovmöller diagrams of SSHAs are not shown because they can be referred to the work of Li et al (2007), who showed a similar space-time SSHA structure in the NSCS. Unlike that work, however, the SSHA values in the Hovmöller diagram analyzed here are cross-shore means of the high-pass filtered SSHAs in the selected area (the rectangular box in Fig.1), where the SSHO 4 resides.…”
Section: Space-time Structure Of Ssho4mentioning
confidence: 99%
“…These eddies increase the intraseasonal variation of sea surface height (SSH) (Zhuang et al, 2010). Documented periods of SSH intra-annual variation in the NSCS range from 1.5 to 8 months (Wang et al, 2000;Hu et al, 2001;Li et al, 2007). However, the dominant period of SSH intraseasonal variation along the continental slope has not been determined.…”
Section: Introductionmentioning
confidence: 99%